Investigating the role of self-construal in the formation of entrepreneurial intentions - Zampetakis, Leonidas A.; Kafetsios, Konstantinos; Lerakis, Manolis; Moustakis, Vassilis (Frontiers in Psychology, 2015)
Individuals may perceive themselves as independent and distinct from others or as interdependent and connected to others. Do these differences in self-construal influence entrepreneurial preferences and intentions to start a new business in university students? Few studies have examined the influence of cultural orientations on entrepreneurial intentions at the individual level of analysis. Two studies investigated the role of independent and interdependent self-construal within the theory of planned behavior (TPB). In the first study, results from structural equation modeling analyses found that chronic independent self-construal was related to attitudes towards entrepreneurship and moderated relationships between attitudes and entrepreneurial intentions. In the second study, participants primed with an independent self-construal had more favorable entrepreneurial attitudes, but not intentions than participants primed with an interdependent focus. This set of studies extends cognitive models of entrepreneurship by demonstrating the role of self-construal in the TPB model at individual level.